El Salvador : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This paper presents an assessment of financial sector stability in El Salvador. The findings reveal that the financial system of El Salvador was resilient in the face of the global shocks and political uncertainty that took a toll on the economy in 2009. The new stand-by arrangement with the IMF bolstered confidence in the new authority's policies and eased concern over the limited lender-of-last-resort capacity of the central bank. Despite the adverse economic environment of 2009, banks' capitalization and liquidity remain high, and stress tests indicate that most banks could withstand severe shocks. Regulated nonbanks are also sound, but pension funds' poor profitability could pose a problem in the longer term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet